The Effect of Environmental Personality and Gender On Studentsâ€™ Ecological Footprint - Herdie Idriawien Gusti (IJEEM - Indonesian Journal of Environmental Education and Management, 2017)
Since environmental issue is often discussed, our ecosystem is getting more fragile. At the same time, basic human needs should be full filled fast by improving productivity and of course this will require natural resources. Indicator for this is exactly could be seen as to what extent human being has changed his/her consumer behavior, in term of how fast he/she utilize space available at a given ecosystem. This measurement called â€œecological footprint (EF).â€ How studentsâ€™ EF affected by environmental personality and gender is research problems of this study. An ex post facto method has been applied by involving 258 faculty of technology students (115 male and 143 female), State University of Jakarta as a sample. Environmental Personality (EP) measured based on â€œbig-five personalityâ€ related to environmental issues such as openness, conscientiousness, extraversion, agreeableness, and emotional stability (30 items, only 19 was valid and its reliability was .74) and EF refers to measure of water, transportation, foods, and others, utilized by students in daily life. Data have been analyzed by one-way ANOVA, F-test, t-test and chi-square. The research results reveal that there is significant difference (Î± = .10) of students EF between students who high, medium, and low in EP. It means that EP did affect students EF. If male and female students EP were separated, again gender did affect students EF which come up with the interpretation that gender equality was neglected in higher educational system. Moreover, it was found that EP does not affect as a single factor, but it depends on studentsâ€™ gender as well because there is significant dependency between EP and students gender in determining students EF (X2-cal > X2-table). Based on those finding, it could be recommended that some factors such as students locus of control, personal responsibility, situational factors, or intention to act with other models of research could be taken into consideration. In future research, to make sure that EF might not been affected by a single factor.